2022
DOI: 10.52711/0974-360x.2022.00216
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficacy of Capparis spinosa Total flavonoids to control Bird Lice (Menacanthus stramineus)

Abstract: The present study included an in-vitro and in-vivo insecticidal investigation for one of wild Iraqi plant Capparis spinosa total flavonids on locally chicken lice (Menacanthus stramineus). Extraction of total flavonoids from 115g of fresh plant samples by reflex extraction with 600ml distilled water with (10% v/ v) HCl, for 8 hours continuously and the aglycon part was obtained with ethyl acetate. The acetate layer was dried and the residue was weighted and subjected for qualitative and quantitative analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…The study of [15] revealed that the extract of the crude terpene compounds of C. spinosa had influences on the death and growth period of the small grain borer Rhizopertha dominica, where the cumulative mortality rate of the non-mature stages increased was 100% as a result of the treatment with the two concentrations of 5 and 10 mg/ml from both the leaf and fruit extracts, whereas the control treatment caused a rate of 22.2%. The results of the present investigation agree with those reported by [16], who tested the impacts of the crude extract of C. spinosa at concentrations of (50, 25, 12.5) mg/ml on the bird lice insect, where the mortality rate of nymphs reached 100%. The results presented here are also consistent with those reported by [15] who examined the influences of the alcoholic extract of Moringa oleifera on the insect Oryzaephilus.surinamensis.…”
Section: Effects Of the Concentrations Of The Leaf And Root Alcoholic...supporting
confidence: 92%
“…The study of [15] revealed that the extract of the crude terpene compounds of C. spinosa had influences on the death and growth period of the small grain borer Rhizopertha dominica, where the cumulative mortality rate of the non-mature stages increased was 100% as a result of the treatment with the two concentrations of 5 and 10 mg/ml from both the leaf and fruit extracts, whereas the control treatment caused a rate of 22.2%. The results of the present investigation agree with those reported by [16], who tested the impacts of the crude extract of C. spinosa at concentrations of (50, 25, 12.5) mg/ml on the bird lice insect, where the mortality rate of nymphs reached 100%. The results presented here are also consistent with those reported by [15] who examined the influences of the alcoholic extract of Moringa oleifera on the insect Oryzaephilus.surinamensis.…”
Section: Effects Of the Concentrations Of The Leaf And Root Alcoholic...supporting
confidence: 92%